An efficient strategy to boost the directed migration of photogenerated holes by introducing phthalocyanine as a hole extraction layer. Issue 15 (24th June 2022) - Bu, Qijing; Zhao, Qifeng; Lu, Guang; Zhu, Xixi; Zhang, Yuexing; Xie, Tengfeng; Liu, Qingyun; Jiang, Jianzhuang
Abstract : Phthalocyanine with adjustable band energy and a binding group acts as a hole extraction layer to accelerate hole transfer from Ti-Fe2 O3 to CoPi, and thus improves the PEC water oxidation performance of Ti-Fe2 O3 . Abstract : Although the sluggish water oxidation kinetics could be optimized by the decoration of cocatalysts, the transport of photogenerated charges in the bulk photoanodes is still a critical bottleneck in cocatalyst modified semiconductor photoanodes. Herein, we have firstly proposed the concept of modulating the photogenerated charge migration in the bulk photoanode by inserting phthalocyanine as the hole extraction layer between the semiconductor (Ti-Fe2 O3 ) and the cocatalyst (CoPi). Benefitting from the gradient band structure of Ti-Fe2 O3, metal-free 2, 3, 9, 10, 16, 17, 23, 24-octacarboxy phthalocyanine (H2 Pc(COOH)8 ) and CoPi, as well as the coplanar binding mode of Ti-Fe2 O3 and H2 Pc(COOH)8, the photogenerated holes of Ti-Fe2 O3 would be migrated directionally to CoPi through H2 Pc(COOH)8, hence more photogenerated holes arrive at CoPi and participate in the water oxidation reaction. As expected, the triphasic photoanode (CoPi/Pc/Ti-Fe2 O3 ) exhibits not only a higher photocurrent density but also a more negative onset potential than CoPi/Ti-Fe2 O3 .